Provenance Variation in Phenology and Frost Tolerance in Subalpine Fir (Abies lasiocarpa) Planted in Denmark and Iceland - Brynjar Skulason; Ole Hansen; Ulrik Nielsen (Forests, 2018)
In Iceland and Denmark, there is an interest in planting Abies lasiocarpa for use as Christmas trees. To search for usable genetic material for both countries, 26 provenances of subalpine fir, covering most of its natural range, were planted in eastern Iceland and Jutland, Denmark. Flushing, bud set and survival rates were assessed. Artificial freezing of twigs, from field trials in eastern Iceland and Denmark, was done to rank the provenances for frost tolerance in the spring and autumn. The northernmost provenances showed earliest bud set, highest autumn frost tolerance and a latitudinal cline was delineated. Differences between provenances in flushing and spring frost tolerance were less than that found for bud set and autumn frost tolerance. The southernmost provenances showed earliest flushing and the most spring frost damage on buds. Mortality of single provenances in the field tests could not be attributed to low freezing tolerances in the autumn or spring. The southernmost provenances of Abies lasiocarpa from New Mexico and Arizona showed the highest survival rate in the field trial in East Iceland, while the eastern provenances showed a low survival rate except for two provenances from Utah and Wyoming. The western provenances from Washington state showed the best survival in Denmark, followed by the southernmost provenances.